Update 2014: Advances to Optimize 6-Mercaptopurine and Azathioprine to Reduce Toxicity and Improve Efficacy in the Management of IBD. Issue 2 (February 2015) - Amin, Jaimin; Huang, Brian; Yoon, Jessica; Shih, David Q.
Abstract : Background: The thiopurine drugs, 6-mercaptopurine (6-MP) and azathioprine (AZA), remain as a mainstay therapy in inflammatory bowel disease (IBD). Differences in metabolism of these drugs lead to individual variation in thiopurine metabolite levels that can determine its therapeutic efficacy and development of adverse reactions. In this update, we will review thiopurine metabolic pathway along with the up-to-date approaches in administering thiopurine medications based on the current literature. Methods: A search of the PubMed database by 2 independent reviewers identifying 98 articles evaluating thiopurine metabolism and IBD management. Results: Monitoring thiopurine metabolites can assist physicians in optimizing 6-MP and AZA therapy in treating patients with IBD. Of the dosing strategies reviewed, we found evidence for monitoring thiopurine metabolite level, use of allopurinol with thiopurine, use of mesalamine with thiopurine, combination therapy with thiopurine and anti–tumor necrosis factor agents, and split dosing of AZA or 6-MP to optimize thiopurine therapy and minimize adverse effects in IBD. Conclusions: Based on the currently available literature, various dosing strategies to improve therapeutic response and reduce adverse reactions can be considered, including use of allopurinol with thiopurine, use of mesalamine with thiopurine, combination therapy with thiopurine and anti–tumor necrosis factor agents, and split dosing of thiopurine. Abstract : Article first published online 22 September 2014.